2010
DOI: 10.1051/limn/2010028
|View full text |Cite
|
Sign up to set email alerts
|

Influences of habitat type and environmental variables on benthic macroinvertebrate communities in a large shallow subtropical lake (Lake Taihu, China)

Abstract: -We investigated benthic macroinvertebrate communities in three contrasting habitats of a large shallow lake from February to November 2009. The three habitats differed markedly in their environmental characteristics (e.g., trophic status, substrate type, wind exposure). A total of 36 species were collected from the three habitats. The calculated descriptors (abundance, biomass and Pielou evenness index) differed significantly among the habitats. Generally, Tubificidae, Bivalvia and Gastropoda dominated the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 43 publications
(50 reference statements)
5
29
0
3
Order By: Relevance
“…To our knowledge, the first detailed work was in 1987À1988 (Huang 2001), during which four comprehensive investigations were conducted in the whole lake and a total of 59 taxa were recorded. The results of Cai et al (2011Cai et al ( , 2012a and Ji et al (2012) showed that only about 40 taxa were recorded and macrozoobenthic assemblages differed significantly among habitats and different lake parts. Cai et al (2012b) also found that the present benthic community in Meiliang Bay of Lake Taihu has simplified substantially compared to communities in 1994.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…To our knowledge, the first detailed work was in 1987À1988 (Huang 2001), during which four comprehensive investigations were conducted in the whole lake and a total of 59 taxa were recorded. The results of Cai et al (2011Cai et al ( , 2012a and Ji et al (2012) showed that only about 40 taxa were recorded and macrozoobenthic assemblages differed significantly among habitats and different lake parts. Cai et al (2012b) also found that the present benthic community in Meiliang Bay of Lake Taihu has simplified substantially compared to communities in 1994.…”
Section: Introductionmentioning
confidence: 94%
“…Due to the great spatial heterogeneity in environmental conditions, we divided Lake Taihu into four parts with contrasting habitat conditions to study the long-term changes of macrozoobenthic assemblages: (1) the River Mouth (TH0, TH6, and TH10), located near three main tributary rivers which were used to assess the influence of the main nutrient inputs; (2) the North Bay (including Meiliang Bay and Zhushan Bay), suffered severe seasonal algal blooms and exhibited high nutrient levels in the water column and surface sediment; (3) the Open Lake characterized by intensive wind-wave disturbance due to its long wind fetch and the bottom covered by a thin layer of mud-sand sediment containing lower nutrient concentrations; and (4) the East Bay characterized by abundant submerged macrophytes and clear water, with relatively low phytoplankton concentrations (Qin et al 2007;Cai et al 2011Cai et al , 2012a Figure 1). …”
Section: Study Area and Site Descriptionmentioning
confidence: 99%
“…Some previous studies have shown that there was a positive effect of macrophytes on benthic macroinvertebrate assemblages (Hargeby et al, 1994;Żbikowski and Kobak, 2007;Cai et al, 2011). Generally, macrophytes can provide habitats and foods for aquatic animals, which can increase spatial heterogeneity and allow more species of various ecological niches to coexist in a macrophytedominated lake (Padial et al, 2009;Bazzanti et al, 2010;Robinson and Doering, 2013).…”
Section: Relationship Between Benthic Macroinvertebrate Assemblages Amentioning
confidence: 99%
“…Therefore, it's necessary to reveal factors determining the taxonomic composition and structure of macroinvertebrates in the open water zone of shallow lakes (Żbikowski and Kobak, 2007). It has been shown that benthic macroinvertebrate distribution is affected by sediment quality, contaminants, biotic factors, N o n -c o m m e r c i a l u s e o n l y oxygen conditions and macrophytes (Mackay, 1992;Phipps et al, 1995;Dinsmore and Prepas, 1997;Weatherhead and James, 2001;Cai et al, 2011). In addition, macroinvertebrate indices have been used frequently for evaluating aquatic ecosystem health combined with water quality monitoring (Song et al, 2007;Gabriels et al, 2010;KeizerVlek et al, 2012;Clews et al, 2014;Traversetti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation